ANALISIS PENGGUNAAN TEKNOLOGI AUGMENTED REALITY SEBAGAI PENGUATAN LITERASI DIGITAL PADA PEMBELAJARAN IPA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SD SKOW SAE - Ria Ristiani; Tiffany Shahnaz Rusli; Hidayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research analyzes the use of Augmented Reality (AR) technology to strengthen digital literacy in natural science education and its effect on student motivation at SD Inpres Skow Sae. The research method used was Concurrent Mixed Methods, involving 32 fifth-grade students. Quantitative data were collected through a learning motivation questionnaire, and qualitative data were gathered through observation and interviews. The results showed that the use of AR had a significant and positive impact on student motivation. The average motivation score reached 87.5 out of an ideal score of 100, with 68.75% of students in the "very high" category and 31.25% in the "high" category. The statistical hypothesis test, which showed a significance value of 0.037 (< 0.05), clearly proves that this increase in motivation was not coincidental. Qualitatively, interviews confirmed these findings, with students expressing that AR made difficult subjects easier to understand and more interactive, changing their perception of science to be more positive and enjoyable. Data triangulation revealed a strong convergence between the questionnaire and interview results, confirming that the increase in motivation was reflected not only in the scores but also in changes in learning behavior that were more active, independent, and enthusiastic. Thus, this study concludes that AR is a proven transformative solution for overcoming educational challenges in remote areas, effectively boosting motivation while simultaneously fostering behaviors aligned with the digital era.